Volatile organic compounds inhibiting effect on the photosynthetic pigments content in woody plants seedlings leaves - Tulkova Elеna G. (Journal of the Belarusian State University. Ecology, 2020)
The article presents the results of determining the photosynthetic pigments content in the seedlings leaves of the most common representatives the urban environment tree plants – the hanging birch Betula pendula Roth. and poplar pyramidal Populus pyramidalis Roz. – in the given experimental conditions. It was established that the toxic effect on hanging birch pigments the o-xylene and benz (a) pyrene suspended solution manifested itself after one day of the experiment; butyl acetate and a mixture of butyl acetate with o-xylol – after three days treatment. The response of the pyramidal poplar was characterized by a decrease in the content of photosynthesis pigments after three days after the introduction of all the solutions used. The maximum change in the pigment content during the experiment in hanging birch caused the action of butyl acetate; pyramid poplar – benz (a) pyrene; and the greatest change in the pigment content compared with the control was noted under the action of o-xylol and a mixture of butyl acetate with o-xylol in birch hanging, and in pyramidal poplar under the influence of o-xylol and benz (a) pyrene.